2022
DOI: 10.1002/cam4.4547
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of malignant cells and novel therapeutic targets revealed by single‐cell sequencing in lung adenocarcinoma

Abstract: Background Single‐cell transcriptomics has been used to investigate various tumors to elucidate the molecular distinction of all cell type compositions of a complex mix. Aims This study aimed to investigate malignant‐cell‐specific genes to explore diagnostic and therapeutic biomarkers using single‐cell transcriptomic data of lung adenocarcinoma. Materials & Methods 10X single‐cell RNA‐seq data of fourteen patients with lung adenocarcinoma were analyzed. Genes that expressed differentially and those with higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…2B). Among TTF-1, EPCAM, CK7 (or KRT7) and MUC1, more genes of the cytokeratin's family were found either in the tumoral primary cells or in the PDTs (KRT6A, KRT8, KRT18 and KRTCAP3) 27 . Genes such as NAPSA and S100P were observed in our Vasc-PDT in accordance with the tumoral primary cells.…”
Section: Resultsmentioning
confidence: 99%
“…2B). Among TTF-1, EPCAM, CK7 (or KRT7) and MUC1, more genes of the cytokeratin's family were found either in the tumoral primary cells or in the PDTs (KRT6A, KRT8, KRT18 and KRTCAP3) 27 . Genes such as NAPSA and S100P were observed in our Vasc-PDT in accordance with the tumoral primary cells.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent analysis validated the independent predicted value and well performance in immunotherapy response and revealed the crucial role of immune cells within the TME in tumor progression and metastasis. Since the rapid development and accessibility of scRNAseq in cancer research, promising findings in cancer evolu-tion, metastasis, and TME have been reached [21,22]. Previous studies have demonstrated that single-cell transcriptome analysis could apply specific signature genes to estimate cell type abundances of bulk transcriptome [23].…”
Section: Discussionmentioning
confidence: 99%
“…Patient records lacking survival information were removed ( n = 22). The Human Protein Atlas ( https://www.proteinatlas.org ) [ 19 , 20 ] data on gene localization was retrieved. Gene locations, including their main location, additional location, and extracellular location, are all included in the data that was retrieved from the database.…”
Section: Methodsmentioning
confidence: 99%